2012
DOI: 10.1080/10426914.2011.585497
|View full text |Cite
|
Sign up to set email alerts
|

Enabling and Understanding Ultrasonic Machining of Engineering Ceramics Using Parametric Analysis

Abstract: Ultrasonic machining (USM) on ceramics is highly demanded in the present industry because of its wide and potential uses in various fields in modern industries. Experiments based on central composite second-order rotatable design have been conducted on ultrasonic drilling of hexagonal shaped hole on high alumina ceramic. RSM was employed for developing empirical models. Analysis on machining characteristics of ultrasonic drilling operation was made based on the developed models. In this study, abrasive grit si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…[1,2]. Tungsten carbide-cobalt composite (WC-Co) possesses a perfect blend of high hardness and superior toughness for desired characteristics such as wear=abrasion resistance, toughness, and dimensional stability, as it is composed of tungsten carbide grains in the matrix phase and cobalt as binder (reinforcement).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. Tungsten carbide-cobalt composite (WC-Co) possesses a perfect blend of high hardness and superior toughness for desired characteristics such as wear=abrasion resistance, toughness, and dimensional stability, as it is composed of tungsten carbide grains in the matrix phase and cobalt as binder (reinforcement).…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical model for maximizing the volumetric MRR (mm 3 /s) was also developed as given in Eq. (15). …”
Section: Examplementioning
confidence: 95%
“…The optimization performance of TLBO algorithm was compared with that of GA, SA, ABC, PSO, HS and shuffled frog leaping (SFL) algorithms, and it was observed that TLBO algorithm showed the best optimization performance. Lalchhuanvela et al [15] considered abrasive grit size, slurry concentration, power rating, tool feed rate and slurry flow rate as the predominant USM process parameters, and determined the optimal combination of those process parameters for maximum MRR and minimum SR using a response surface methodology (RSM)-based multi-objective optimization technique. In a follow-up paper, using RSM, Lalchhuanvela et al [16] studied the effects of the above-mentioned process parameters on profile accuracy of machined hexagonal holes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lalchhuanvela et al [2] presented a study of the MRR and surface roughness in machining of ceramics (alumina based). It was reported that the higher level of every input parameter gives higher MRR.…”
Section: Introductionmentioning
confidence: 99%
“…Power rating and abrasive grit size are the main significant factors which affect the MRR and TWR [1][2][3][4][5][6][7]. Lalchhuanvela et al [2] presented a study of the MRR and surface roughness in machining of ceramics (alumina based).…”
Section: Introductionmentioning
confidence: 99%